Biobutanol production from hydrolysates of cyanobacteria Lyngbya limnetica and Oscillatoria obscura - Kushwaha D.; Srivastava N.; Prasad D.; Mishra P.K.; Upadhyay S.N. (My University, 2025)
The potential of hydrolysates of cyanobacteria Lyngbya limnetica and Oscillatoria obscura for biobutanol production was evaluated under varying operating conditions using Clostridium beijerinckii ATCC 35702 culture as the fermenting microrganism. Effects of various process parameters affecting the biobutanol production were investigated using glucose as the C-source. The maximum biobutanol productivity of 1.565 g/L/d was obtained with L. limnetica biomass hydrolysate supplemented with 10.0 g/L of glucose under the best conditions in batch mode. The large biobutanol production (8.873 g/L) was obtained with glucose supplemented hydrolysate while the highest yield (0.421 g/g sugar) was found with pure cyanobacterial hydrolysate indicating its industrial feasibility. The hydrolysates prepared from biomass of L. limnetica and O. obscura grown following a two-stage protocol, were utilized for the first time for biobutanol fermentation and nearly 33.0 and 31.0% increased biobutanol productivities, respectively, were obtained under the best operating conditions. Results of the agitated bioreactor studies were analysed by fitting the data into the Mercier's kinetic model and the high value of regression coefficients (≥0.93) indicated excellent agreement between the experimental values and model predictions. The results were also used to present a metabolic pathway and carry out a mass balance analysis for biobutanol fermentation. © 2020 Elsevier Ltd